Laparoscopic vs. open surgery for the treatment of iatrogenic colonoscopic perforations: a systematic review and meta-analysis. Issue 1 (December 2017) - Martínez-Pérez, Aleix; de'Angelis, Nicola; Brunetti, Francesco; Baleur, Yann; Payá-Llorente, Carmen; Memeo, Riccardo; Gaiani, Federica; Manfredi, Marco; Gavriilidis, Paschalis; Nervi, Giorgio; Coccolini, Federico; Amiot, Aurelien; et al.
Abstract Aims Iatrogenic colonoscopy perforations (ICP) are a rare but severe complication of diagnostic and therapeutic colonoscopies. The present systematic review and meta-analysis aims to investigate the operative and post-operative outcomes of laparoscopy vs. open surgery performed for the management of ICP. Methods A literature search was carried out on Medline, EMBASE, and Scopus databases from January 1990 to June 2016. Clinical studies comparing the outcomes of laparoscopic and open surgical procedures for the treatment for ICP were retrieved and analyzed. Results A total of 6 retrospective studies were selected, including 161 patients with ICP who underwent surgery. Laparoscopy was used in 55% of the patients, with a conversion rate of 10%. The meta-analysis shows that the laparoscopic approach was associated with significantly fewer post-operative complications compared to open surgery (18.2% vs. 53.5% respectively; Relative risk, RR: 0.32 [95%CI: 0.19–0.54;p < 0.0001; I2 = 0%]) and shorter hospital stay (mean difference −5.35 days [95%CI: −6.94 to −3.76;p < 0.00001; I2 = 0%]). No differences between the two surgical approaches were observed for postoperative mortality, need of re-intervention, and operative time. Conclusion The present study highlights the outcomes of the surgical management of an endoscopic complication that is not yet considered in clinical guidelines. Based on the current available literature, the laparoscopic approach appears to provide better outcomes in terms of postoperative complications and length of hospital stay than open surgery in the case of ICP surgical repair. However, the creation of large prospective registries of patients with ICP would be a step forward in addressing the lack of evidence concerning the surgical treatment of this endoscopic complication.